Feasibility Study of Pinhole Inspection via Magnetic Flux Leakage and Hydrostatic Testing in Oil & Gas Pipelines. Issue 2 (January 2021) - Zhang, Hailiang; Sha, Shengyi; Willis, Chris; Qingshan, Feng; Chen, Pengchao
Abstract: Oil & Gas pipeline pinhole leaks are more likely to lead to serious consequences than larger leaks because they are difficult to discover through conventional monitoring and patrolling. An undetected pinhole leak can lead to significant soil and groundwater pollution over time. The effectiveness and applicability of magnetic flux leakage (MFL) in characterizing and sizing pinhole defects is studied by pull test in a 10-inch pipe string with manufactured defects. MFL technologies from five vendors were tested in blind scenarios. In addition, the feasibility of using hydrostatic testing to detect pinhole defects is investigated. The results show that the MFL signal may be affected by pinhole diameter, depth, position, and so on. An optimal practice was developed by comparing the gap between MFL tracks, sampling frequency, intensity of magnetic field, etc. And there was no significant reduction in pressure capacity within the test pipe segment with pinhole. So it is speculated that hydrostatic testing can only identify pinholes that have fully penetrated the pipe wall.